Lipase and protease production from Jatropha curcas cake : A review - Nurul Iwani, Alawi; Khairul Farihan, Kasim; Mohamed Zulkali, Mohamed Daud, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Universiti Malaysia Perlis (UniMAP), 18th - 19th July 2009 at Dragon & Pheonix, Jejawi, Arau, Perlis, Malaysia.